ESTIMATING VALUE WHEN BALANCING REAL ESTATE OF AGRICULTURAL ENTERPRISES IN THE REPUBLIC OF SERBIA - Majstorović, Aleksandar; Petrović, Vesna; Vukša, Slavko (Economics of Agriculture, 2016)
The frst aim of this paper is to analyze the possibilities that an appropriately created and positioned function of fnancial estate management opens up for an agricultural enterprise and its signifcance for optimal balancing of estate in a companys total assets. Since estates often represent a signifcant position in the assets, it is necessary to repeatedly reassess the value of the agricultural companys estates by using an appropriate methodology, and that task is often assigned to an audit. If the values of particular positions of estate determined in the process of reevaluation differ signifcantly from the positions in the balance of assets, it is necessary to carry out corrections in fnancial reports. Depending on the degree of correction, an assessment is carried out and a contribution to the quality of fnancial reports is made. The importance of this paper stems from the fact that it presents a methodology of an agricultural companys estate value reassessment and gives a model of how, based on determined differences, one can assess quality of fnancial statements in the area of estate balance policies.